2007
DOI: 10.1080/00016340601089768
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in patients with previous uterine rupture

Abstract: Longitudinal ruptures and short intervals between rupture and subsequent pregnancy predispose to recurrence of uterine rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 16 publications
3
51
3
3
Order By: Relevance
“…Lim et al (2005) did not report any repeat ruptures in their case-series. However, Usta et al (2007) had an incidence of 34% repeat rupture in their study in Beirut, Lebanon. The initial ruptures in Cases 3 and 4 could have been avoided if an elective caesarean section had been done.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Lim et al (2005) did not report any repeat ruptures in their case-series. However, Usta et al (2007) had an incidence of 34% repeat rupture in their study in Beirut, Lebanon. The initial ruptures in Cases 3 and 4 could have been avoided if an elective caesarean section had been done.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies and case reports have reported favourable outcomes in subsequent pregnancies after uterine rupture (Al Sakka et al 1999;Lim et al 2005;Usta et al 2007). All these studies recommended planned caesarean delivery for the subsequent pregnancy, even though the exact timing of delivery is not generally agreed on.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…CT scan is performed when there is doubt about the diagnosis or location of the abscess [4] . The patients should be treated with broad-spectrum parenteral antibiotics [6,7] . Aspiration of abscess under ultrasound guide depends on its site [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen articles were found [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (references [31] and [32] reported the same cases). Full-text articles reporting about subsequent fertility and pregnancy after complete uterine rupture were retrieved.…”
Section: Literature Reviewmentioning
confidence: 99%